1997
DOI: 10.1177/004051759706701107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chelating Agents and Mechanical Pretreatment on Enzymatic Retting of Flax

Abstract: Adding chelating agents, i.e., oxalic acid and ethylenediamine-tetra-acetic acid (edta), substantially increases the retting effect on flax by the commercial enzyme products Ultrazym and Flaxzyme (Novo Nordisk), as shown by scanning electron microscopy, release of reducing sugars, and the Fried test. Degradation of pectin-rich citrus peel by these enzymes also increases with the addition of oxalic acid and edta, while citric acid has a low or insignificant effect. Oxalic acid at 50 mmol concentration reduces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 7 publications
0
73
0
Order By: Relevance
“…Each sample of 7 g of flax straws was rinsed with distilled water and then crushed twice with a 700 g rod to maximize retting performance by increasing the exposure of phloem regions along stems (Henriksson et al 1997). Subsequently, the sample was placed into a 250 mL glass bottle, and distilled water was added in a ratio of 1:33.…”
Section: Water Rettingmentioning
confidence: 99%
“…Each sample of 7 g of flax straws was rinsed with distilled water and then crushed twice with a 700 g rod to maximize retting performance by increasing the exposure of phloem regions along stems (Henriksson et al 1997). Subsequently, the sample was placed into a 250 mL glass bottle, and distilled water was added in a ratio of 1:33.…”
Section: Water Rettingmentioning
confidence: 99%
“…Previous research has indicated that acidic pectins and Ca 2+ are located preferentially in the epidermal regions of Linum usitassimum (flax) (Rihouey et al 1995), contributing to the structural integrity of the stem and bast fibres. Therefore, chelators, such as EDTA, have the ability to remove Ca 2+ and enhance retting of flax (Henriksson et al 1997(Henriksson et al , 1999. The variability in the pectin content along with Ca 2+ in different fibres might influence the retting efficiency in the presence or absence of EDTA.…”
Section: Metal Ions Comentioning
confidence: 99%
“…Kompolti) for fibre production was grown according to 35°C and pH 4.5. EDTA was added to the incubation medium to destabilize pectins by complexing cell wall bound calcium [7,8,9]. After 4 h fibres were removed from solution, rinsed twice using tap water, centrifuged, and air-dried for 2 to 3 d. There were two independent preparations (prep1, prep2).…”
Section: Plant Materialsmentioning
confidence: 99%